2018
DOI: 10.18203/2394-6040.ijcmph20180762
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitude regarding organ donation and transplantation among undergraduate medical students in North coastal Andhra Pradesh

Abstract: Background: Organ transplantation is one of the greatest scientific advances and remains one of the most challenging and complex field of modern medicine. In the USA and UK, the organ donation rate is 26 and 14 per million, whereas in India, it is only 0.34 per million population. Healthcare professionals act as the critical link in the organ procurement process because they are the first individuals to establish relationship with the potential donors' family.Methods: An institution based descriptive cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 6 publications
2
7
0
Order By: Relevance
“…Research suggests that the education level of health professionals is positively related to their personal willingness to donate organs (Schaeffner, Windisch, Friedel, Breitenfeldt, & Wolfgang, 2004). The positive effect of education level has been studied in various populations and may have a direct influence on attitudes toward organ donation (Ozdag, 2001;Ganta et al, 2018;Srivasta & Mani, 2018). The results of both us and other studies are very encouraging in terms of emphasizing the importance of education.…”
Section: Conclusion and Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Research suggests that the education level of health professionals is positively related to their personal willingness to donate organs (Schaeffner, Windisch, Friedel, Breitenfeldt, & Wolfgang, 2004). The positive effect of education level has been studied in various populations and may have a direct influence on attitudes toward organ donation (Ozdag, 2001;Ganta et al, 2018;Srivasta & Mani, 2018). The results of both us and other studies are very encouraging in terms of emphasizing the importance of education.…”
Section: Conclusion and Discussionmentioning
confidence: 60%
“…The common characteristics of organ donors are being young, well-educated and having a high socio-economic status (Ozdag, 2001). Studies in literatures indicated that cadaveric organ donation rates are quite high in countries, which place importance to education about organ donation and are able to create a level of awareness about this issue in society (Ganta et al, 2018;Srivasta & Mani, 2018). In addition to that, comparisons between east-west or developed-developing countries determined that in all societies younger people compared to older people, women compared to men, well educated people compared to less educated people have a more positive view regarding organ donation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organ transplantation is one of the greatest scientific advances and remains one of the most challenging and complex field of modern medicine. The World Health Organization (WHO) defines organ donation as the gift of an individual's body parts after their demise for transplantation (Ganta, Pamarthi, & K, 2018). The present study provides several important insights into the knowledge and awareness of organ donation among newly admitted 1 st MBBS students of Medical College.…”
Section: Discussion:-mentioning
confidence: 80%
“…In this study, it was interesting to see that almost 99% of the participants were aware about organ donation, which was similar to the findings in the study by Srinivas Rao G et. al [9]. This can be attributed to high literacy rate in the state of Kerala.…”
Section: Discussionmentioning
confidence: 99%